Solutions to the cocktail party problem in insects: selective filters, spatial release from masking and gain control in tropical crickets. - Arne K D Schmidt; Heiner Römer (PLoS ONE)
Background Insects often communicate by sound in mixed species choruses; like humans and many vertebrates in crowded social environments they thus have to solve cocktail-party-like problems in order to ensure successful communication with conspecifics. This is even more a problem in species-rich environments like tropical rainforests, where background noise levels of up to 60 dB SPL have been measured. Principal findings Using neurophysiological methods we investigated the effect of natural background noise (masker) on signal detection thresholds in two tropical cricket species Paroecanthus podagrosus and Diatrypa sp., both in the laboratory and outdoors. We identified three 'bottom-up' mechanisms which contribute to an excellent neuronal representation of conspecific signals despite the masking background. First, the sharply tuned frequency selectivity of the receiver reduces the amount of masking energy around the species-specific calling song frequency. Laboratory experiments yielded an average signal-to-noise ratio (SNR) of -8 dB, when masker and signal were broadcast from the same side. Secondly, displacing the masker by 180° from the signal improved SNRs by further 6 to 9 dB, a phenomenon known as spatial release from masking. Surprisingly, experiments carried out directly in the nocturnal rainforest yielded SNRs of about -23 dB compared with those in the laboratory with the same masker, where SNRs reached only -14.5 and -16 dB in both species. Finally, a neuronal gain control mechanism enhances the contrast between the responses to signals and the masker, by inhibition of neuronal activity in interstimulus intervals. Conclusions Thus, conventional speaker playbacks in the lab apparently do not properly reconstruct the masking noise situation in a spatially realistic manner, since under real world conditions multiple sound sources are spatially distributed in space. Our results also indicate that without knowledge of the receiver properties and the spatial release mechanisms the detrimental effect of noise may be strongly overestimated.